Kesan Pembinaan Bandar Baru Tunjong, Kota Bharu, Kelantan Terhadap Kawasan Petempatan Penduduk (Kesan Banjir Kilat) - Anuar, Nur Balqis; mohamed, Sulzakimin (Research in Management of Technology and Business, 2021)
In Malaysia, flash floods often occur due to a combination of nature and human action. The problem of flash floods in the study area has disrupted the daily activities of residents, property damage, traffic congestion and so on. The objective of this study is to study the impact of flash floods due to the construction of new cities on residential areas, identify the causes of flash floods and identify measures to overcome the flash floods. In this study, questionnaires and interviews were used to obtain the required information. The result of this study is to meet all the objectives of the study so that the problem of flash floods can be overcome. Therefore, this study has been able to study in more depth about the increasingly serious problem of flash floods and effective measures to control it can be implemented.